The Influence of Affective State on Subjective-Report Measurements: Evidence From Experimental Manipulations of Mood - Askim, Kine; Knardahl, Stein (Frontiers in Psychology, 2021)
A substantial portion of the knowledge base of psychology is based on subjective reports with a risk of information bias. The objective of the present study was to elucidate one contextual source of variance and potential bias in subjective reports: the influence of affective state at the time of responding to questionnaires. Employees (N = 67, abstaining from stimulants and activities that may influence emotional and physiological state) were subjected to mood-induction procedures in the laboratory. Neutral, positive, and negative moods were induced by combinations of pictures from the international affective picture set (IAPS) and music. The subjects responded to questions on visual analog scales (VAS) in order to optimize sensitivity and attenuate short-term memory effects. Most subjects exhibited significant affective-state inductions with no change in arousal. The analyses took affective response to the manipulation into account. Only four of 20 questions were somewhat influenced by induced affective state: job overload, social support from co-workers, satisfaction with getting to develop personally, and an item measuring agreeableness. In general, responding to questions of work that were phrased for valence was little or insignificantly influenced by induced affective state.